Extraction and Spectrophotometric Determination of Iron(III) with N-(o-methyl) Phenyl-N-Hydroxy-N1-(o´ -Methyl)Phenyl- Benzamidine Hydrochloride and Thiocyanate - Mishra, Alok; Hemlata Mohabey, (Ms) (Asian Journal of Chemistry, 2010)
N-(o-methyl) phenyl-N-hydroxy-NI-(o-methyl) phenyl-benzamidine hydrochloride is proposed as a new reagent for selective extraction and spectrophotometric determination of iron(III) in presence of thiocyanate. The orange-red mixed complex is formed which is extractable into benzene. The optimum acidity range for the extraction and spectrophotometric determination of the complex is 0.25 M to 0.6M. Molar absorptivity and Sandell's sensitivity of the complex at its λmax (470nm) have been found to be 11480 L mole–1 cm–1 and 0.0047 cm–2 respectively. The system obeys Beer's law in the range 0.4 ppm to 4 ppm and interference due to the presence of a number of cations and anions have been studied and the method is successfully applied to determine iron content in a number of iron drugs, soil samples and iron ores.